Comparative analysis of cassava and sweet potato improved processing techniques in Nigeria: rural women experience (2004)
One of the major products obtained form cassava and sweet potato is 'gari'. It is widely utilized and common. Economic recession in Nigeria has made 'gari ' a more valuable food, especially for the poor in the urban areas. The present and future prospect of cassava and sweet potato processing depends more upon the developments of improved processing technologies that can increase labour productivity and of improved products that can meet the changing need of the rural and urban dwellers to replace the age-long traditional processing techniques. The aim of this study is to compare the cassava and sweet potato improved processing techniques for products generation. A total of 320 women were randomly selected and interviewed from the Agricultural Development Projects states in South western Nigeria with the use of interview schedule Inferential statistics and descriptive statistical tools were used in analyzing the data. The results showed that the same improve processing technologies used for cassava processing are used for sweet potato processing and the most widely used improved processing technologies include abrasive peeler, sieve, motorized grater, screw jack or hydraulic press. Cassava and sweet potato products include "spari", "lafun", starch and "fufu". A major conclusion in this paper is that sweet potato "spari" is slightly darker than the cassava and it is cyanide free unlike cassava "gari", which needs to be processed to remove the cyanide contents. Furthermore, there is no difference in the processing techniques of cassava and sweet potato.